2007
DOI: 10.1194/jlr.m700047-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Perilipin regulates the thermogenic actions of norepinephrine in brown adipose tissue

Abstract: In response to cold, norepinephrine (NE)-induced triacylglycerol hydrolysis (lipolysis) in adipocytes of brown adipose tissue (BAT) provides fatty acid substrates to mitochondria for heat generation (adaptive thermogenesis). NE-induced lipolysis is mediated by protein kinase A (PKA)-dependent phosphorylation of perilipin, a lipid droplet-associated protein that is the major regulator of lipolysis. We investigated the role of perilipin PKA phosphorylation in BAT NE-stimulated thermogenesis using a novel mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…There are data suggesting that there are nonnociceptive visceral receptors on sympathetic afferent cell bodies within the DRG of the thoracic and more rostral lumbar spinal levels that are involved in the reflexive homeostatic control of the viscera (14). In the present context, such visceral information could include information on IBAT lipolysis, as lipolysis within brown adipocytes is necessary for its thermogenic function (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are data suggesting that there are nonnociceptive visceral receptors on sympathetic afferent cell bodies within the DRG of the thoracic and more rostral lumbar spinal levels that are involved in the reflexive homeostatic control of the viscera (14). In the present context, such visceral information could include information on IBAT lipolysis, as lipolysis within brown adipocytes is necessary for its thermogenic function (57).…”
Section: Discussionmentioning
confidence: 99%
“…That is, lipolysis via phosphorylation of hormone-sensitive lipase and perilipin A is necessary for catecholamine-induced lipolysis in both WAT and BAT (for review see Ref. 4) and for BAT, it is necessary for its thermogenic response (57).…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing lipolysis in Plin1-null and wild-type mice revealed that Plin1-null adipocytes had increased rates of constitutive (unstimulated) lipolysis and reduced catecholamine-stimulated lipolysis (70). In these cells, Plin2 replaced Plin1 protein on the LD, which suggests that Plin2 is less efficacious in blocking basal adipocyte lipolysis (70,72). Nelifinavir, an anti-HIV drug, has been reported to promote lipodystrophy in humans (73), and we demonstrated that it specifically enhanced Plin1 degradation by a lysosomal pathway in mouse adipocytes, resulting in increased rates of constitutive basal lipolysis.…”
Section: Role Of Ld Proteins In Obesity-associated Insulin Resistancementioning
confidence: 99%
“…Brown adipocytes also express Plin1. In recent studies using lines of transgenic and Plin1-knockout mice, we demonstrated that the mutation of the six consensus PKA sites of Plin1 from serine to alanine blocked catecholamine-stimulated lipolysis and brown fat thermogenesis (72). Thus, in adult mice, LD proteins regulate BAT metabolism and thermogenesis.…”
Section: Role Of Ld Proteins In Obesity-associated Insulin Resistancementioning
confidence: 99%
“…Numerous studies have shown that PLIN plays an important role in regulating lipid metabolism in humans, mice, cows, and chickens (Marcinkiewicz et al, 2006;Brasaemle, 2007;Miyoshi et al, 2007;Souza et al, 2007;Zhao et al, 2009;Fan et al, 2010), which are important references in the study of duck fat metabolism. Currently, researchers have cloned the PLIN gene of humans, mice, cattle, and chickens, but there are no reports about this gene in duck.…”
Section: Introductionmentioning
confidence: 99%